Introduction to the physical chemistry of foods - Ritzoulis, Christos (Taylor & Francis, 2013)
"This book provides an introduction to the physico-chemical basis and mathematical description of notions such as distillation, crystallization, sublimation, protein denaturation, emulsions, kinetics, enzymatic activity, and rheology. It lays the foundations in explaining the texture of ice cream, the foaming of beer, and the stability of milk, correlating fundamental physico-chemical concepts such as freezing, distillation, (re)crystallization, foaming, emulsification, aggregation and clarification to their applications in the fields of processing, microbiology and bioavailability of foods. Special attention has been paid so that the content is easily accessible by readers with basic background knowledge of physics, mathematics and chemistry"-- Provided by publisher.
Keywords: Food -- Analysis.; Food -- Composition.; Chemistry, Technical.; elektronické knihy; electronic books